The idiosyncratic impact of an aggregate shock the distributional consequences of COVID-19 - Low, H; Benzeval, M; Burton, J; Crossley, T; Fisher, P; Jäckle, A; Read, B (University of Oxford, 2020)
Using new data from the Understanding Society: COVID 19 survey collected in April 2020, we show how the aggregate shock caused by the pandemic a?ects individuals across the distribution. The survey collects data from existing members of the Understanding Society panel survey who have been followed for up to 10 years. Understanding society is based on probability samples and the Understanding Society Covid19 Survey is carefully constructed to support valid population inferences. Further the panel allows comparisons with a pre-pandemic baseline. We document how the shock of the pandemic translates into di?erent economic shocks for di?erent types of worker: those with less education and precarious employment face the biggest economic shocks.Some of those a?ected are able to mitigate the impact of the economic shocks: universal credit protects those in the bottom quintile, for example. We estimate the prevalence of the di?erent measures individuals and households take to mitigate the shocks. We show that the opportunities for mitigation are most limited for those most in need.